MAKRO - AND НАНО SCALE REMEMBERING SYSTEMS ON THE BASIS STIMULUSSENSITIVE OF POLYMERS - Yergogin, Ye. Ye.; Suleimenov, I. E.; Mun, G. A.; Volzhenin, D. V.; Hvan, O. V.; Myzhanova, N. (Recent Contributions to Physics, 2009)
In work it is shown that in well-known systems – stimulus-sensitive to polymers – are inherent the hysteresis phenomena and hence they can be used for creation of memories, in particular, trigger screens. The conclusion is drawn that remembering systems can be realised also on the basis of separate molecules stimulus-sensitive, in particular, thermosensitive polymers. The role of such systems for developmentnanoelectronics is discussed.
Keywords: trigger screens